(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article considers the dynamics of the indicators of the innovation index of the Kyrgyz Republic in the fields of education and science, presented in the studies of the Global Innovation Index GII for 2015-2023. One of the levers of stabilization and development of the economy of the Kyrgyz Republic is the activation of innovation activities with the wide use of intellectual property. Currently, high-level innovation experts conduct intensive research on global innovation development in the world, which is organized and coordinated jointly by three authoritative organizations and institutes - the World Intellectual Property Organization, the World Business School and Cornell University. These organizations annually publish the research results in the form of books called «Global Innovation Index» in English. The article analyzes the indicators of the innovation index of the Kyrgyz Republic in the sections of education and science GII 2016-2024, and also considers the comparative characteristics of these indicators of the global innovation index of a number of countries, including the CIS countries. The strong and weak indicators of the innovation index of the Kyrgyz Republic were analyzed, and based on the results of these studies, recommendations were proposed to improve the country’s innovation indicators, which will contribute to the socio-economic development of the country